Clothing of urban-poor a case study of five selected families in Payatas, Quezon City - Ulanday, Maria Elena Benedicta Sharon Prado; Mayo, Aelaida Villaraza (1997.)
This research is a case study of the clothing aspects of five purposely selected urban-poor families in Payatas, Quezon City. Its main purpose is to gain insight of the clothing families belonging to the marginalized section of the society. Data gathered include families' clothing inventory, budgetary allocation for clothing, the method of acquisition, clothing habits, practices and care, and lastly, to determine their clothing problems. A multi-method gathering of data was conducted to obtain the clothing aspects of each of the family: series of informally unstructured in-depth interviews using guides, observations and clothing inventory thru guides and checklists. The study is descriptive in nature, thus content analysis and photocriticism was done to analyze the data gathered. The major findings of the study were: 1. The clothing inventory consists mainly of basic articles of clothing items in limited quantity. 2. There was no definite budgetary allocation and pre-planning for their clothing needs. 3. The method of acquisition was mainly through shopping in cash at the nearest clothing store mostly in "tiangge" and "bangketa" or flea market at least once a year especially the holiday season or whenever there is still money left on hand. 4. Clothing practices, habits, care and problems such as poor quality of clothing items purchased, inadequate rinsing of clothes when laundrying, not immediately repairing or mending torn clothes to name a few, were mainly attributed to lack of consumer knowledge and skills and their inaccessibility to to basic services like water and education due to their limited and irregular family income and other resources. Further intensive and extensive studies of this nature should be undertaken for whatever purpose the data gathered may serve in the field of production, marketing, consumer education, social work and the like. Moreover, research in clothing of other social or economic group may also be conducted for documentary and comparative studies. Inclusion of atleast basic clothing knowledge and skills such as sewing, mending or repair in the home economics or practical arts curriculum in the primary level of education is also recommended.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Clothing and dress; Dressmaking